Управління системами поставки бетону в умовах сухого і жаркого клімату - Саль, Аднан Абу (Ways to Improve Construction Efficiency, 2014)
Dissertation is devoted research of bases of providing of buildings concrete mixtures in the conditions of dry and hot climate in Jordan. On the basis of different connection of the most widespread in practice methods and facilities of mechanization at preparation, transporting and drafting of concrete mixture were developed 12 the most characteristic technological charts of production of concrete works in the conditions of dry and hot climate. Using the methods of mathematical statistics analytical dependences (for every chart) of the resulted cost were made 1 м3 to concrete mixture ot power and type of concrete factory, type of vehicles of transports, distance of transporting, cost of processing of constituents, methods of drafting and other Introduction of job in practice of building performances will let to promote quality of concrete constructions and obtain the decline of cost 1 мЗ constructions to 10-15%.